2012
DOI: 10.4238/2012.march.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Brazilian and introduced olive germplasms based on microsatellite markers

Abstract: ABSTRACT. Olive trees have been grown since the beginning of civilization, and the consumption of olives and olive products is increasing worldwide, due to their health benefits and organoleptic qualities. To meet the growing market for olives, commercial cultivation of this species is expanding from traditional areas to new regions. Although the Brazilian olive industry has just begun to be established, breeding programs are already developing cultivars that are more adapted to local conditions. We used 12 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
8
1
1
Order By: Relevance
“…The efficiency of using Bayesian statistics for the genetic diversity and populations structure analyses is well-known and has been used in different crops, such as olive (do Val et al, 2012), coffee (Setotaw et al, 2010), and strawberry (Nunes et al, 2013). In our study, the 94 accessions were grouped into three clusters that agreed with the geographical distribution of the populations.…”
Section: Discussionmentioning
confidence: 57%
“…The efficiency of using Bayesian statistics for the genetic diversity and populations structure analyses is well-known and has been used in different crops, such as olive (do Val et al, 2012), coffee (Setotaw et al, 2010), and strawberry (Nunes et al, 2013). In our study, the 94 accessions were grouped into three clusters that agreed with the geographical distribution of the populations.…”
Section: Discussionmentioning
confidence: 57%
“…The synonyms and homonyms among fruit trees have been widely reported [104][108]. Several previous studies noted several synonyms and homonyms in the olive collection, making it difficult to identify the reference of olive cultivars [29], [36], [53], [96], [100], [109][112]. Our results indicated that a number of accessions known by the same names were genetically different, suggesting that these were homonyms.…”
Section: Discussionmentioning
confidence: 58%
“…Slightly higher PIC values (0.47 to 0.91) were registered by Belaj et al [31] between local cultivars and wild olive trees from 3 important Spanish olive-growing regions. Do Val et al [100] reported that the informativeness of the 12 loci (PIC) were highly variable (0.12–0.72), of which eight loci showed PIC values ≥0.50. These results are partially similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Oleaster genotypes were admixed much more with the ancient than with the current olive cultivars ( Figure 2C,D). The analysis of molecular variance (AMOVA) performed to evaluate the partitioning of molecular variance among native cultivars, oleasters, and foreign olive cultivars, showed that 93% of variation is due to genetic variation within groups, with only 7% of genetic variance being observed among groups, indicating the high heterozygous nature and mixed genetic structure of the olive genotypes [47]. The calculated PhiPT (analogue of Fst index) (0.074) was significant, p < 0.001, indicating low genetic differentiation among groups.…”
Section: Genetic Structure and Principal Coordinate Analysismentioning
confidence: 99%